Household Migration and Child Educational Attainment: The Case of Uganda - Lucia Ferrone; Gianna Claudia Giannelli (Institute for the Study of Labor (IZA), 2015)
In many Sub-Saharan African countries, a large number of people migrate internally or abroad because of demographic, economic and political factors. This pronounced mobility is likely to have consequences for child education, which is still a matter of concern in the region. We study this issue for Uganda, investigating whether the migration of household members affects child primary education and in what direction. Using the Uganda National Panel Survey for 2005, 2009, 2010 and 2011, we estimate conditional fixed effects logit models of school attendance and primary school completion. We find that migration of children has a significant positive impact on child school attendance rates while that of adults has a significantly negative effect, and that remittances have no influence. These findings suggest that migration of children is indeed beneficial, since it may contribute to matching the demand and supply of schooling. The absence of adults, instead, has controversial effects when children are left behind. In fact, lack of supervision and children working substituting adults in their tasks might reduce the rate of school attendance. However, the migration of neither children nor adults seem to increase the rate of primary school completion, evidence that points to the problem of the low quality of primary education in developing countries.
Keywords: I25; J13; J61; O15; 330; migration; schooling; panel data models with fixed effects; Uganda